Direct to public peer support and e-therapy program versus information to aid self-management of depression and anxiety: protocol for a randomized controlled trial - Kaylor-Hughes, Catherine; Rawsthorne, Mat; Coulson, Neil S.; Simpson, Sandra; Simons, Lucy; Guo, Boliang; James, Marilyn; Moran, Paul; Simpson, Jayne; Hollis, Chris; Avery, Anthony; Tata, Laila J.; et al. (Journal of Medical Internet Research, 2017)
Regardless of geography or income, effective help for depression and anxiety only reaches a small proportion of those who might benefit from it. The scale of the problem suggests a role for effective, safe, anonymised public health driven online services such as Big White Wall which offers immediate peer support at low cost. Objectives: Using RE-AIM methodology we will aim to determine the population reach, effectiveness, cost effectiveness, and barriers and drivers to implementation of Big White Wall (BWW) compared to online information compiled by the UK’s National Health Service (NHS Choices Moodzone) in people with probable mild to moderate depression and anxiety disorder. Method/Design: A pragmatic, parallel group, single blind RCT is being conducted using a fully automated trial website in which eligible participants are randomised to receive either 6 months access to BWW or signposted to the NHS Moodzone site. The recruitment of 2200 people to the study will be facilitated by a public health engagement campaign involving general marketing and social media, primary care clinical champions, healthcare staff, large employers and third sector groups. People will refer themselves to the study and will be eligible if they are over 16 years, have probable mild to moderate depression or anxiety disorders and have access to the internet. The primary outcome will be the Warwick-Edinburgh Mental Well-being Scale at six weeks. We will also explore the reach, maintenance, cost-effectiveness, barriers and drivers to implementation and possible mechanisms of actions using a range of qualitative and quantitative methods. Discussion: This will be the first fully digital trial of a direct to public on line peer support programme for common mental disorders. The potential advantages of adding this to current NHS mental health services and the challenges of designing a public health campaign and randomised controlled trial of two digital interventions using a fully automated digital enrolment and data collection process are considered for people with depression and anxiety.